Analiza podejść do rozumienia struktury i funkcji świadomości etycznej = Analysis of approaches to understand the structure and functions of ethical consciousness of the personality - Ševčenko, Natalia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the analysis of psychological approaches to understanding the structure and functioning of individual ethical consciousness. The concepts of moral and ethical consciousness have been specified. The moral consciousness is a form of social consciousness; it is based on a social being and is objective. Ethical consciousness means comprehension of morality by a personality and represents a form of individual consciousness.
Keywords: świadomość etyczna; świadomość moralna; refleksja moralna; czyn moralny; ethical consciousness; moral consciousness; moral reflection; a moral act